Peran Keberadaan Badan Usaha Milik Desa (BUMDes) Terhadap Perekonomian Dan Pengembangan Masyarakat Desa Laut Dendang Menuju Desa Mandiri - Budiyanti Budiyanti; Mita Nalsalisa Br Barus; Vadillah Raihto Hutasuhu; Elsy Nila Sari Situmeang; Rosni Rosni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research examines the role of Village-Owned Enterprises (BUMDes) in improving the economy and developing society in Laut Dendang Village, with the ultimate goal of achieving independent village status. Using a qualitative method with a case study approach, this research analyzes the contribution of BUMDes in creating jobs, increasing people's income, and facilitating access to resources and training. The research results show that the existence of BUMDes has had a significant positive impact on local economic growth, increasing community skills, and strengthening village institutional capacity. BUMDes plays a role as a catalyst in the process of village economic empowerment, which ultimately helps Laut Dendang Village move towards independence. However, this research also identifies challenges faced, including limited capital and government support, which need to be overcome to optimize the role of BUMDes. These findings provide insight for the government and other stakeholders in designing more effective policies and strategies for village development through BUMDes.